“Potassium Competitive Acid Blocker”- new Weapon to Combat Acid Peptic Disorders - Islam, M M Shahin Ul (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Abstract not available Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):72-73